Protein Prenylation in Plants: Mechanisms and Functional Implications - Chang Tian; Quan Wang (Plants)
Protein prenylation is a crucial post-translational modification that involves the formation of a covalent bond between isoprenoid lipids and the cysteine residues of specific proteins. This modification plays a significant role in determining protein localization, facilitating protein–protein interactions, and ultimately influencing protein function within the cellular context. Prenylation is a conserved process observed across various kingdoms of life, including plants, animals, fungi, and protists. This review aims to consolidate existing knowledge regarding the mechanisms underlying protein prenylation, encompassing the biosynthetic pathways of isoprenoids in plants and the processing involved in the prenylation modification. Furthermore, it highlights the implications of alterations in protein prenylation on plant development, signaling pathways, and stress responses. The review also addresses the similarities in modification mechanisms between plants and animals, as well as the diversity of their functional implications. Finally, it outlines prospective research directions of the plant prenylation mechanisms and the potential applications in the field of biotechnology.